METODE PEMBELAJARAN MENURUT AL-QUR’AN SURAH AN-NAHL AYAT 125 - Suganda, Suganda; Lasahia, Sudin; Suanah, Suanah; Nurfaizah, Nurfaizah; Fahmi, Sri; Alimah, Sri (STAI Darul Qalam Tangerang, 2025)
The learning method is one method that can foster learning activities for students, and efforts to choose a good learning method improve the quality of teaching or education that will be their responsibility. Because this learning method aims to make it easier for a teacher to achieve certain goals. This study discusses the learning method in the Al-Qur'an Surah An-Nahl verse 125 using the Tafsir of the Al-Qur'an. This study was conducted to determine how the learning method in the Al-Qur'an Surah An-Nahl verse 125 through the analysis of Ibn Kathir's interpretation. And to find out whether verse 125 of the An-Nahl surah is about the educational method. This study includes library research (Library Research) using a qualitative descriptive method with an Tafsir approach, namely interpreting the verses of the Al-Qur'an related to the theme or title of the discussion. The data collection method is carried out using the documentation method. This method can be interpreted as a way of collecting data by utilizing data in the form of books. Data were taken from literature sources, namely primary sources including Ibn Kathir's interpretation while secondary sources were books, journals, and those related to the title. And using content analysis. The results of this study concluded that the learning method in the Al-Qur'an Surah An-Nahl verse 125 according to Ibn Kathir's Interpretation there are three learning methods, namely: the Hikmah method (good words), the Mau'idzah Hasanah method (good advice), and the Jidal method (debate).